2018
DOI: 10.1111/jep.12953
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the weekend upon admissions to General Medicine

Abstract: General Medicine has an inpatient mortality unaffected by the DOWOA. Care efficiency, however, follows a weekly cycle. The "weekend effect" for General Medical inpatients is a prolongation in their IPLOS as a result of fewer weekend discharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Although the variability in overall activity statewide is striking, individual hospitals may have quite different experiences. Additionally, the data set is only from New York State; there may be some differences in other states based on hospital and patient characteristics, although the findings here are consistent with experience elsewhere [9][10][11][12][13][14][15][16][17]. As this study did not include pediatric, psychiatric, or obstetric patients, the findings are not generalizable to these populations.…”
Section: Limitationsmentioning
confidence: 48%
See 2 more Smart Citations
“…Although the variability in overall activity statewide is striking, individual hospitals may have quite different experiences. Additionally, the data set is only from New York State; there may be some differences in other states based on hospital and patient characteristics, although the findings here are consistent with experience elsewhere [9][10][11][12][13][14][15][16][17]. As this study did not include pediatric, psychiatric, or obstetric patients, the findings are not generalizable to these populations.…”
Section: Limitationsmentioning
confidence: 48%
“…Previous studies have shown that elective or scheduled admissions drive the variability of day-to-day admissions, with most elective admissions occurring at the beginning of the week. Studies have also shown fewer discharges on the weekend and increased LOS for patients who are discharged after the weekend [9][10][11][12][13][14][15][16][17]. However, these studies were conducted in only one or a few hospitals, studied certain diagnoses, and did not include both medical and surgical cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important source for creating evidence-based information that will increase the quality of healthcare service is health information technology infrastructure. Most studies in the literature are based on surveys, direct observations, or retrospective calculations from records of wait times 13,[19][20][21][22] . According to a study published in 2017, the studies on the calculation of wait times in hospitals based 1on the process records of health service delivery are very rare 1 .…”
Section: Introductionmentioning
confidence: 99%